Transformative role of artificial intelligence in enhancing occupational health and safety: A systematic review and meta-analysis - Karadağ, Turabi (The European Research Journal, 2025)
Objectives: This study aims to systematically review and analyze the impact of artificial intelligence (AI) technologies on occupational health and safety (OHS), focusing on their effectiveness in risk mitigation, disease prevention, and the promotion of worker well-being. Methods: A comprehensive literature search was conducted across databases including Embase, PubMed, and Google Scholar, covering studies from 1974 to the present. The review followed the guidelines set forth by Cochrane, with data analyzed using the Review Manager software (Version 5.4). Results: The analysis included 25 studies involving diverse industries, with a total of 2,500 workers. Findings indicated a significant positive effect of AI technologies on reducing occupational hazards (SMD: -0.75, 95% CI: -0.82 to -0.68, Z=18.45, P<0.00001) and enhancing safety protocols (SMD: -0.45, 95% CI: -0.56 to -0.34, Z = 9.30, P<0.00001). Furthermore, AI-driven monitoring tools were associated with a notable decrease in workplace accidents (SMD: -0.52, 95% CI: -0.60 to -0.44, Z = 14.23, P<0.00001). Conclusions: The integration of AI in occupational health and safety practices significantly enhances the management of workplace risks, leading to improved safety outcomes and reduced incidents. This study underscores the need for continued investment in AI technologies to promote healthier and safer work environments.